The Effect of Search, Solve, Create, And Share (SSCS) Learning Model towards Student’s Critical Thinking Skills - Milama, Burhanudin; Bahriah, Evi Sapinatul; Mahmudah, Amaliyyah (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract The aim of this study is determine the effect of search, solve, create, and share (SSCS) learning model on critical thinking skills of hydrocarbons and petroleum material. The method used in this study was quasi experimental design, with research design nonequivalent control group design. The sample was taken by purposive sampling and divided into two groups consist of control group and experimental group. The data gathering techniques in this study was through 8 items of essay test instrument which is analyzed by using t-test. The results of t-test data showed that tcount  ttable or 16.36  1.980 at significance level 5%, value tcount lies in the region reject H0 and accept Ha. The result shows that there are significant search, solve, create, and share (SSCS) learning model on student’s critical thinking skills. Keywords: Search, Solve, Create, and Share (SSCS) Learning Model, Critical Thinking Skills; Hydrocarbons and Petroleum.